The 14th Annual AMSE Conference - Mozaffar Partowmah (International Institute of Islamic Thought, 1988)
The 14th Annual Conferknce of the Association of Muslim Scientists and Engineers (ASME) was held during the weekend of qufur 2628, 1409/0ctober 7-9, 1988, at the Islamic Center of North America in Plainfield, Indiana. Papers presented at the Conference dealt with a variety of subjects ranging from agriculture and health sciences to car manufacturing tips, computers, industrial, civil and electronic engineering, as well as resource management and organizational behavior. Members of the AMSS (Association of Muslim Social Scientists) who attended the AMSE Conference, participated in the sessions with undivided attention. Dr. AbdulHamid AbuSulayman, the AMSS President, in his banquet speech, stressed the need for an active AMSE that will eventually attract a more sizable number of Muslims in North America and coordinate their scientific efforts for their common benefit. In a session entitled “Technology Transfer,” the Japanese and Korean approaches were contrasted with the Muslim world approach. A highlight of the Conference was the announcement of the A1 Khwarazmi Award that the AMSE will award annually to a distinguished Muslim scientist or engineer. The first Al Khwarazmi Award went to Dr. M.A.K. Lodhi of Texas A&M University in appreciation of his continuous support for Muslim students and his long-time involvement in the AMSE in addition to his scientific interest and achievements in nuclear physics and field theory. The Best Student Paper Award went to the following: 1) Abdullah M. Elramsisi of Rochester Hill, Michigan for his paper “On Model-based Image Restoration and Performance Evaluation;” and 2) Khatib Rajab of Morgantown, West Virginia for his paper on “Agricultural Research Needs and Priorities in Zanzibar as perceived by Administrators and Extension Workers.” Copies of all of the presented papers were distributed at the Conference and will be ppblished in the conference proceedings. Preprints and reprints may be obtained by writing to the AMSE office at P.O. Box 38, Plainfield, Indianna, 46168 ...